1999
DOI: 10.3354/meps176131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc on the life-cycle, growth and reproduction of the marine amphipod Corophium volutator

Abstract: The effects of zinc concentrations on the life-history, growth and reproduction of Corophium volutator (Pallas, 1766) were investigated Amphipods were exposed for 100 d to 4 sublethal zinc concentrations (0.2, 0.4, 0.6 and 0.8 mg I-') Except for the highest concentration tested, zinc exposure did not affect the life-span of C. volutator, although the number of surviving amphipods decreased with increasing concentrations. Life expectancy at the end of the experiment differed at the various zinc exposure concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…The present study demonstrated that the female amphipods were more sensitive than the males in terms of growth and that toxic effects could be neglected if both males and females were not used in the experiment or measured independently. In the natural environment, this delay in growth of female amphipods could consequently impair the reproduction of the population, because organisms need to reach a certain size before reproduction can occur [49] and larger organisms produce larger broods than smaller individuals [50]. A plausible explanation for this observation is the difference in response of female and male amphipods and the fact that they were not measured separately.…”
Section: Growthmentioning
confidence: 99%
“…The present study demonstrated that the female amphipods were more sensitive than the males in terms of growth and that toxic effects could be neglected if both males and females were not used in the experiment or measured independently. In the natural environment, this delay in growth of female amphipods could consequently impair the reproduction of the population, because organisms need to reach a certain size before reproduction can occur [49] and larger organisms produce larger broods than smaller individuals [50]. A plausible explanation for this observation is the difference in response of female and male amphipods and the fact that they were not measured separately.…”
Section: Growthmentioning
confidence: 99%
“…For the amphipod C. volutator a standardized protocol for acute marine sediment toxicity has been created under the auspices of the Oslo and Paris Commissions (PARCOM, 1993) and given its wide use and amount of toxicological information, can be considered an European ''benchmark'' species (in the sense of Chapman, 1995). Yet, most of the published studies with C. volutator still concern only acute sediment toxicity (Ciarelli, Vonck, & van Straalen, 1997;Grant & Briggs, 2002;Matthiessen et al, 1998) and very few considered chronic exposures or other endpoints than survival and burrowing behavior (e.g., Ciarelli, Vonck, van Straalen, & Stronkhorst, 1998;Conradi & Depledge, 1999). Therefore, despite the growing use of sediment toxicity tests as a fundamental component of ecotoxicological assessments, and the enormous scientific effort devoted to them in the last decade, the new generation (Moore & Dillon, 1993) of chronic marine and estuarine sediment tests is yet to be developed, at least in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors that are crucial as regards intraspecific variation in reproductive traits include salinity, food availability, temperature and the presence of toxic substances (e.g. Kinne 1970Kinne , 1971Kolding and Fenchel 1981;Conradi and Depledge 1999;Maranhão et al 2001;Eriksson Wiklund et al 2008).…”
Section: Introductionmentioning
confidence: 99%